Analisis Multidimensional untuk Pencegahan Disparitas Gizi pada Anak Balita - Ivan Panji Teguh; Ervina, Anis; Nicki Yuke Syahrani D (Prodi DIII Kebidanan La Tansa Mashiro, 2024)
The nutritional status of children under five is an important indicator in determining the quality of public health and is the main focus of nutrition prevention. This study aims to analyze multidimensional factors associated with disparities in nutritional status of children under five years of age based on indicators of body weight for age (BB/U), body length for age (PB/U), and body weight for body length (BB/PB). The study used a cross-sectional design with a total of 250 under-fives as research subjects. Data were collected through structured interviews, anthropometric measurements, and analysis of consumption patterns. The results showed that 12.6% of under-fives were underweight based on BB/U, while 12.6% of under-fives were stunted based on PB/U, and 12.1% of under-fives were wasted based on BW/PB. Statistical analysis revealed that a history of low birth weight (LBW), history of complementary feeding, fruit and vegetable consumption patterns, gender, and access to health facilities had a significant association with the nutritional status of under-fives. In contrast, the habit of consuming sweets did not show a significant relationship with the nutritional status of children under five in all three indicators. These results corroborate the theory that the nutritional status of children under five is influenced by various multidimensional factors, including biological, behavioral, and environmental factors. This study recommends strengthening education to parents about the importance of balanced nutrition, strengthening access to health services, and community-based nutrition program interventions to prevent nutritional disparities in children under five. Collaborative efforts across sectors are key in ensuring optimal growth and development of children under five and preventing the long-term impact of nutritional problems.